2023
DOI: 10.1159/000528039
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlates of Lifetime Voice-Hearing in Patients with Borderline Personality Disorder: A Pilot Study

Abstract: <b><i>Introduction:</i></b> Auditory verbal hallucinations (AVH) are transdiagnostic phenomena that can occur in several mental disorders, including borderline personality disorder (BPD). Despite the transdiagnostic relevance of these symptoms, very little is known about neural signatures of AVH in BPD. <b><i>Methods:</i></b> We used structural magnetic resonance imaging to investigate multiple markers of brain morphology in BPD patients presenting with a lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…However, it is worth noting that we found the hypergyrification of the orbitofrontal cortex to be specific to schizophrenia patients with treatment-resistant auditory verbal hallucinations. Although not in schizophrenia, a similar result was reported by Kubera et al (2023), who observed hypergyrification of the left lateral orbitofrontal cortex in borderline personality disorder patients with auditory verbal hallucinations as compared with non-hallucinating patients. Ren et al (2022) found lower cortical thickness in the bilateral lateral orbitofrontal cortices in schizophrenia patients with persistent auditory verbal hallucinations, which is somewhat consistent with our findings, considering that gyrification and cortical thickness tend to have an opposing relationship (Hogstrom et al 2013; Gautam et al 2015).…”
Section: Discussionsupporting
confidence: 85%
“…However, it is worth noting that we found the hypergyrification of the orbitofrontal cortex to be specific to schizophrenia patients with treatment-resistant auditory verbal hallucinations. Although not in schizophrenia, a similar result was reported by Kubera et al (2023), who observed hypergyrification of the left lateral orbitofrontal cortex in borderline personality disorder patients with auditory verbal hallucinations as compared with non-hallucinating patients. Ren et al (2022) found lower cortical thickness in the bilateral lateral orbitofrontal cortices in schizophrenia patients with persistent auditory verbal hallucinations, which is somewhat consistent with our findings, considering that gyrification and cortical thickness tend to have an opposing relationship (Hogstrom et al 2013; Gautam et al 2015).…”
Section: Discussionsupporting
confidence: 85%